Careers in astronomy in Germany and the UK - Fohlmeister, Janine; Helling, Christiane (Astronomy & geophysics, 2014)
Janine Fohlmeister and Christiane Helling discuss the outcomes of surveys addressing the career situation of astronomers in Germany and the UK, finding social and cultural differences between communities as well as gender bias in both.
Gesehen am 30.09.2020